Utilization of the experimental data to test ionic water/graphene nanofluids for solar applications by means of CVFEM simulation - Abeer S. Alnahdi; Muhammad Sulaiman; Malik Zaka Ullah; Taza Gul (Case Studies in Thermal Engineering)
Experimental data is used in this study to investigate the enhancement of renewable energy in a solar collector using nanofluid with graphene oxides and ionic nanofluids. High-accuracy numerical analysis is achieved by using the Control Volume Finite Element Method in combination with Homotopy-Analysis-Method to simulate the solar collector design. The main features of this model include the effects of nanoparticle volume fraction, solar thermal radiation, heat source sink, and three-dimensional thin film flow model in terms of an inclined plane with variable thickness of the thin film. Superior thermal energy efficiency has been observed in a nanofluid containing pure ionic liquid and graphene oxide with the combinations including ionic liquid–water (75–25 %)/graphene oxide, ionic liquid–water (50 %–50 %)/with graphene oxide, and water with graphene oxide. The results obtained confirmed the experimental values by obtaining the improvements of 9.001 %, 36.8 %, and 72.8 %. Graphene Oxide/Ionic Hybrid nanofluid used for a solar energy system is a novel way to contribute, considering the three-dimensional thin film flow over an inclined plane with new similarity transformations.